Quality characteristics of Trabzon persimmon dried at several temperatures and pretreated by different methods - Bolek, Sibel; Obuz, Ersel (Tubitak Scientific & Technological Research Council Turkey, 2014)
Although Trabzon persimmon (Diospyros kaki L.) is a beneficial fruit for both human health and industrial use, it is generally used seasonally, and inadequate attention has been given to its off-season use. This study was designed to determine the best drying method for optimizing the quality of dried Trabzon persimmon (Diospyros kaki 'Fuyu'). Samples treated with sodium metabisulfite prior to drying and dried at 65 degrees C had the highest L* value (P < 0.05). Rehydration value and ascorbic acid content of samples dried at 50 degrees C were the highest. Nevertheless, these samples had lower total phenolic content than samples dried at 65 degrees C and 90 degrees C. Samples treated with sodium metabisulfite before drying had the highest appearance score; however, these samples were the least liked and had the lowest flavor score. Control samples were the most popular samples in terms of flavor (P < 0.05). During storage, control group samples had the highest increase in total mesophilic aerobic bacteria, while samples treated with sodium metabisulfite prior to drying had the lowest increase in total mesophilic aerobic bacteria, owing largely to the antimicrobial effect of sodium metabisulfite. Although sodium metabisulfite treatment gave the best physical, chemical, and microbiological results, these dried persimmons were given the lowest sensory scores.
Keywords: Diospyros kaki L.; tray dryer; drying; Trabzon persimmon